(untitled) (Agricultural Engineering, 2019)
The paper carries out a comparative analysis of the production technology of energy willow on plantations varied on account of the surface area in the aspect of the impact on the natural environment. The studies covered the cultivation of willow in the southern part of Poland. Technologies from soil preparation for cultivation to first harvesting and transport to a farm were analysed. A type of the applied technological treatments, used machines and transport means as well as the time of their operation, amount of the consumed fuel, pesticides, fertilizers, and water were taken into consideration. The research results were referred to the surface area of willow cultivation (1 ha). To determine the environmental impact SimaPro program version 8.1.0.60 was used. It was concluded, inter alia, that cultivation of willow on smaller plantations constitutes a bigger environmental footprint.